Effectiveness of Acrylic Acid Based Terpolymer as a Corrosion Inhibitor in Water Treatment - Kamal, Yusoh; W. A. R., Wan Aizan (2003)
A breakthrough in polymer technology has dramatically increased the range of conditions for phosphate-based water treatment programs. Phosphate is good complexing agent whether introduced alone or in combination with other metal cations, eg Zn2+, Mg2+, or Mb2+ in neutral aqueous media. In addition, their hydrolytic stability and scale inhibiting property are reasons why it is widely used as corrosion inhibitors. Results from recent water treatment simulations and used in several chemical plants demonstrated an improved performance. A study was carried out on the corrosion of metal by analyzing the metal immersed in tab water containing zinc polyphosphate in the absence and presence of terpoly (arylamide/acrylic acid/acrylonitrile) with various formulations for a period of five days at 40°C. The effectiveness of the terpolymer in inhibiting the corrosion of metal in water is discussed based on scanning electron microscope (SEM) and weight loss results. A formulation consisting of phosphate-based which is sodium polyphosphate, metal ions (Zn2+), and poly (arylamide/acrylic acid/acrylonitrile) are observed to increase inhibition efficiency, increased tolerance to environmental, and generally longer plant run times.